PENGARUH INFLASI DAN KURS TERHADAP EKSPOR TEH INDONESIA KE JERMAN - Iska Devi; Murtala Murtala (LPPM Universitas Malikussaleh – Indonesia, 2019)
This study aims to determine the effect of inflation and exchange rates on Indonesian tea exports to Germany. The data used in this study are time-series data from 2003 to 2015 obtained from the Central Bureau of Statistics and related agencies. The analytical model used in this study is the Multiple Linear Regression Model. The results of the study partially show that inflation and exchange rates have a positive and significant effect on Indonesian tea exports to Germany. Meanwhile, simultaneously, inflation and exchange rates have no significant effect on Indonesian tea exports to Germany